Peripheral Vascular Calcification in Patients on Regular Hemodialysis in relation to Parathyroid Hormone Abnormalities - Dr. Azzam Hussein Hmoud, Dr. Ibrahim Asi Ali, Dr. Maha Muwafaq Nayyef* (Innovative Journal of Medical and Health Sciences, 2020)
Background: Peripheral vascular calcification (PVC) commonly develop in patients on hemodialysis (HD) and associated with increase risk of morbidity and mortality. Aim of study: To study risk factors of developing peripheral vascular calcification in patients on hemodialysis especially in relation to parathyroid hormone abnormalities. Patients and Methods: Cross sectional (observational) study on 54 patients on regular hemodialysis and divided into 2 groups according to abdominal X-Ray. Results: 54 patient: 32 female, 22 male; mean age = 51.59 +/- 17.61, mean duration of HD = 44.83 +/- 38. 4 months Peripheral vascular calcification by lateral lumbar X-Ray is 12 patients i.e 22.22% We studied effects of many risk factors and appeared significant effects of age, duration of HD and use of calcium containing oral phosphate binders. Also there is some effects of increased serum calcium and phosphate, hypertension and DM but statistically not significant. PTH abnormalities also affect on PVC especially in low level of PTH (a dynamic bone disease) but statistically not significant. In this study, no apparent effect of inflammation on calcification. Conclusion: Peripheral vascular calcification, commonly present in patients on hemodialysis and associated with increase risk of morbidity and mortality, with many risk factors causing increase peripheral vascular calcification which can be prevented and treated